PELITA ASI: Combating stunting through breastfeeding awareness in Gunung Sindur - Indah Permatasari; Tatiana Siregar; Dyah Utari; Ritanti Ritanti; Nelly Febriani (Universitas Muhammadiyah Magelang, 2023)
Stunting can arise due to malnutrition, particularly in the crucial first 1000 days of life. Data from the Bogor District Health Service in 2022 reveals a stunting rate of 9.8 percent in Bumi Tegar Beriman. PELITA ASI is a maternal movement dedicated to nurturing toddlers, aiming to raise awareness among mothers in the prevention of stunting through breastfeeding. The program involves various groups, including cadres, pregnant women, mothers of toddlers, and other potential participants, integrating targeted and sensitive interventions. The primary goal is to enhance the knowledge of cadres and educate mothers of toddlers on the crucial role of breastfeeding in preventing stunting. The success of these activities is evident through a series of well-executed events, marked by a notable increase in participants' knowledge. Pre-test and post-test calculations on 35 participants demonstrated an average knowledge increase of 1.57.